Kajian Kondisi Lahan Mangrove di Desa Bedono, Kecamatan Sayung, Kabupaten Demak dan Kelurahan Mangunharjo, Kecamatan Tugu, Kota Semarang - Zaky, Abdul Rohman; Suryono, Chrisna Adhi; Pribadi, Rudhi (977-2407769)
Mangrove ecosystem have an important role in coastal and marine areas. The existence of these ecosystems in the midst of human life provides many benefits. There are several benefits that are directly or indirectly. Utilization of these ecosystems can slowly lead to a problem that needs to be done the proper management efforts for the utilization of mangrove areas can be done in an optimal and sustainable. One of these management is to evaluate mangrove land condition. The results showed that in both study site physical factor of inundation was the most dominant, while chemical factor even though mostly also similar. Land use and land interaction against current and wave were the most influence factor on mangrove land suitability in Bedono, while in Mangunharjo the most dominant was land use. In term of land suitability for mangrove both Bedono and Mangunharjo were fall into sufficient enough category with physical factors more dominant than the chemicals.